On the accuracy of the pellet analysis method to estimate the food intake in the Antarctic shag, Phalacrocorax bransfieldensis - Casaux, Ricardo Jorge
The possibility to study quantitatively the diet of the Antarctic shag Phalacrocorax bransfieldensis by the analysis of pellets, applying correction factors to compensate for the digestion and loss through the gastrointestinal tract of fish otoliths represented in pellets, was evaluated at two localities of the South Shetland Islands. For such purpose, the results from the analysis of 566 pellets (= regurgitated casts) collected at Harmony Point, and 296 at Duthoit Point, throughout the 1995/96 and 1996/97 breeding seasons, were corrected with the mentioned factors and the shag daily consumption rate was estimated. The estimations indicated that, except for Duthoit Point in 1996/97, the daily food intake increased from November to January (pre-laying to late-rearing) and slightly decreased in February when chicks start to fledge, thus reflecting the energy requirements at the nest. These estimations, in general, are in line with those previously obtained for other colonies and/or shag species by different methods, which suggests that after correction the use of pellets is an acceptable method to quantify the diet of the Antarctic Shag. Fil: Casaux, Ricardo Jorge. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina